Proposal of a methodology for the architectural design of timber houses - Morgado, L. (2015)
This paper presents the principles of a method for the architectural design of timber houses based on the experience gained by timber companies. This proposal has as its major goal the challenging of the scenario of countries like Portugal where a shift in the design and construction methods integrating wood as a material could result in a much more sustainable habitat. A set of interviews was carried out with Portuguese companies in the sector of timber houses. They were questioned about their customers, design methods, the architect’s role and the choice of structural systems. Based on the interviews it was possible to characterize the market and identify the main procedures about design. The most relevant ones were the importance of the architectural type definition, the support of a catalog, the relationship between formal and structural types and the architect’s lack of knowledge about timber. The collected information pointed to an architectural design method to be used by Portuguese architects who, until now have often played a secondary role when a timber house was designed partly because the timber companies dominate the whole process. Some of these companies offer catalogues of design solutions that support customer’s choices. The architects generally reject this type of method because of its supposed uncreative and impersonal results. The method here presented through some basic principles aims at collecting some positive lessons from the catalogue method, defining a process based on the recognition of Formal types and Construction types. This is the framework of a tool intended to help the Portuguese architects to deal with the range of the options available (solutions, companies, structural systems) and a support to help in deciding which construction system to choose.